A green flag for the Flag System? Towards a child protection policy in Flemish sport. Issue 1 (2nd January 2016) - Vertommen, Tine; Toftegaard-Stoeckel, Jan; Vandevivere, Lore; Van Den Eede, Filip; De Martelaer, Kristine
Abstract : Over the past decade, the international agenda on the prevention of child sexual harassment and abuse in sport has been strengthened by a number of general policy recommendations. Despite a growing body of literature and research about sexual harassment and abuse in sport, there is hardly any evidence-based policy and prevention research to guide the policy implementation process. By using the Flemish sport system as its empirical focus, this article investigates the feasibility of the so-called Flag System to translate policy into practice. The Flag System is a didactic tool created to assist sport stakeholders in the assessment of sexual behaviour involving children. It is in the process of being implemented in Flanders, and preliminary findings suggest a high level of feasibility at all levels of organized sports. Demonstrating that a number of inhibiting forces have effectively been reduced in Flanders, the current analysis of the process of planned change suggests that the Flag System has potential in bridging the gap between policy and practice and may also be suitable for implementation in other Western countries.